If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2x = 4 Combine like terms: 5x + -2x = 3x 3x = 4 Solving 3x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 1.333333333 Simplifying x = 1.333333333
| 4p=4p-12 | | -2/5(x-4)=-2 | | 0.5y-0.1(y+3)=0.2(2y+1)-0.7 | | 10+3d=19 | | 13-2m=7 | | 1/2*2/8 | | 0.5y-0.1(y+3)=0.2 | | 4m-23=-27+5m | | y-52/6=5 | | b^0=0 | | b^0=1 | | 8b+12=92 | | 1/2y-7/2=-1/3y-5 | | j-357/18=30 | | b^1=0 | | 20-2k=12 | | x^2+6x-3=-3 | | 80=10(y+5) | | -14x+2(24+4x)=-30 | | 6(g-75)=60 | | 180=(5k-3)+(9+k) | | 0=(3x^2-5x-3)/(x^2-9) | | 34kg=mg | | 56-2r=2 | | 8x=2x*2 | | 4f-11=1 | | 2x-(4-3x)=8 | | e^4x-7*e^3x=105 | | 16a^4-b^4=0 | | 6(x+5)=-3 | | 2x+15=3x^2 | | 15-u=200 |